Novel adjuvants enhance immune responses elicited by a replication-defective human cytomegalovirus vaccine in nonhuman primates. Issue 51 (17th December 2021) - Li, Hualin; Monslow, Morgan A.; Freed, Daniel C.; Chang, Dan; Li, Fengsheng; Gindy, Marian; Wang, Dai; Vora, Kalpit; Espeseth, Amy S.; Petrovsky, Nikolai; Fu, Tong-Ming
Highlights: AdVax and LNP enhanced immune responses elicited by a replication-defective CMV vaccine. Transcriptome analyses of peripheral blood demonstrated different modes of action. LNP induces innate immune response genes; Advax acts via a non-inflammatory mechanism. Abstract: Adjuvants have long been explored to enhance vaccine efficacy. Current adjuvants approved for human vaccines are mostly studied for their ability to improve antibody responses. There remains a need for development of novel adjuvants, especially those able to enhance cell-mediated immunity (CMI). In this preclinical study we assessed the effect of two novel adjuvants, a delta inulin microparticle Advax formulated with or without a toll-like receptor 9 (TLR9) agonist CpG oligonucleotide, and a Merck & Co., Inc., Kenilworth, NJ, USA proprietary lipid nanoparticle (LNP), on immune responses elicited by V160, an experimental replication-defective human cytomegalovirus vaccine. Adult rhesus macaques were immunized with a low dose of V160 (10 units) either alone or in combination with the adjuvants as compared to those immunized with a high dose of V160 alone (100 units). While neither adjuvant conferred a significant benefit to vaccine-elicited humoral immune responses at the dose tested, both enhanced cellular immune responses to V160, where Advax promoted both CD4 +  and CD8 +  T cells and LNP predominantly impacted the CD4 +  T cell response. Transcriptome analyses of peripheral blood samples demonstrated different modes of action for these adjuvants. One day post vaccination, LNP induced upregulation of a large number of genes involved in the innate immune response similar to those triggered by viral infection. In contrast, Advax did not activate any known inflammatory pathways and did not significantly impact gene expression pattern until day 7 post administration, suggesting a unique, non-inflammatory mechanism. These data warrant further exploration of Advax and LNP as adjuvants in clinical trials for vaccines desiring to elicit both humoral and T cell responses.